Answer:
C
Step-by-step explanation:
Given
2x² + x - 1 = 2 ( subtract 2 from both sides )
2x² + x - 3 = 0
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 2 × - 3 = - 6 and sum = + 1
The factors are - 2 and + 3
Use these factors to split the x- term
2x² - 2x + 3x - 3 = 0 ( factor the first/second and third/fourth terms )
2x(x - 1) + 3(x - 1) = 0 ← factor out (x - 1) from each term
(x - 1)(2x + 3) = 0
Equate each factor to zero and solve for x
x - 1 = 0 ⇒ x = 1
2x + 3 = 0 ⇒ 2x = - 3 ⇒ x = -
Answer:
papá fríoStep-by-step explanation:
Answer: 43046721(t^8)
Step-by-step explanation:
So first, multiply 3 by t to get 3t. Then, multiply it again by 3 to get 9t. Raise it to the 8th power to get (9^8)(t^8). This gives you 43046721(t^8)
The domain is the set of all x values which are defined (appear on the graph) of the function. In this system, all values from negative infinity to 0, but not including zero, and all values above zero, through positive infinity, are valid. We can write this in set builder notation as x: (-∞,0)∪(0,∞).
The range is the set of all y values which are defined in the function. Like the domain, the range of this function contains all value from negative infinity to positive infinity except zero. Same notation: y: : (-∞,0)∪(0,∞).
Answer:
2.52= x
Step-by-step explanation: